Foreign body‐associated endobronchial inflammatory polyps - Higashiguchi, Masayoshi (Clin Case Rep, 2018)
Endobronchial polypoid lesions can be observed after removal of a foreign body and usually regress without treatment. Bronchial obstruction with a foreign body can cause atelectasis in nonelderly adults without history of an episode of aspiration.